Malaria: Still no vaccine and very few drugs - Nosten, F; vanVugt, M (1996)
Hopes for the imminent discovery of a vaccine for malaria have receded and drugs will remain of central importance in the treatment of malaria for the foreseeable future. The number of drugs available, however, is very small and the resistance of Plasmodium falciparum is rapidly developing. A coherent strategy for the deployment of antimalarial drugs is urgently needed.